2007
DOI: 10.1007/s00464-007-9364-z
|View full text |Cite
|
Sign up to set email alerts
|

The cost of laparoscopic myotomy versus pneumatic dilatation for esophageal achalasia

Abstract: Initial LM is a more costly management strategy under all clinically plausible scenarios tested in this model. Further research is needed to determine patients' preferences for the two treatment modalities, and society's willingness to bear the incremental cost of LM for those who choose it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 56 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…And they found that PD had a better 5-year efficacy than HM for patients aged > 40 years old (12). In addition, it has been demonstrated that the most cost-effective treatment for achalasia over a 5-10-year period after the procedure is PD (18,19). So, PD is recommended as an initial treatment for achalasia in elderly patients and theoretically leads to a favorable longterm outcome.…”
Section: Discussionmentioning
confidence: 99%
“…And they found that PD had a better 5-year efficacy than HM for patients aged > 40 years old (12). In addition, it has been demonstrated that the most cost-effective treatment for achalasia over a 5-10-year period after the procedure is PD (18,19). So, PD is recommended as an initial treatment for achalasia in elderly patients and theoretically leads to a favorable longterm outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These are mainly young age (<40 years), male gender, single dilation with a 3.0 cm balloon, post-treatment LOS pressure >10–15 mm Hg and poor esophageal emptying on an upright barium oesophagram (timed barium swallow) 9 11 15–18. Pneumatic dilation is the most cost-effective treatment for achalasia over a time period of 5 to 10 years 19 20…”
Section: Pneumatic Dilationmentioning
confidence: 99%
“…The major predictive factors for the failure of EBD treatment include young age (age < 40 years) [1,29], male gender, dilation by using a 30-mm balloon, presence of pulmonary symptoms, failure of treatment after one or two dilation sessions [27,30]. However, EBD is the most cost-effective treatment for achalasia for a period of 5 to 10 years after the procedures [13,31]. The most serious complication is perforation, which occurred in about 1-3% of the cases [5,11], and 50% of those patients required surgical intervention [12].…”
Section: Discussionmentioning
confidence: 99%
“…The most severe complication is perforation, which occurs in about 1-3% of the cases [5,11], 50% of cases requiring surgery [12]. Over a 5-10 year period the balloon dilation is the most cost-effective treatment for achalasia [13]. Decision between these treatment options is difficult to make due to the lack of large randomized controlled trials.…”
mentioning
confidence: 99%